Gestión de administración de los recursos humanos. - Armijos Mayón, Franklin Brian; Bermúdez Burgos, Aaron Isaac (My University, 2020)
This descriptive study of bibliographic review type aims to analyze the management of human resources in business organi-zations, in the current times; was systematized through the methods of scientific research, historical-logical, content analysis and analytical-synthetic. It was determined that human resources are the main asset of a company; The management of human resources is no longer just the selection and hiring of employees, it also has to do with business policies. The Human Resources Department is one of the pyrals of the organizations to define and consolidate in the market; its radius of action includes recruitment, selection, compensation, social benefits, hygiene and safety at work, organizational development, tra-ining and development of personnel, labor relations, database and information systems, and auditing. The management of Human Talent is closely related to the management of human resources; since it structures normative indicators that allow to strengthen the selection, performance, evaluation and personnel training processes.
Este estudio descriptivo de tipo revisión bibliográfica tiene por objetivo analizar la gestión de los recursos humanos en las organizaciones empresariales, en los momentos actuales; fue sistematizado a través de los métodos de investigación científica, histórico-lógico, análisis de contenido y analítico-sintético. Se determinó que los recursos humanos son el principal activo de una empresa; la gestión de los recursos humanos ya no es sólo la selección y contratación de empleados, además tiene que ver con las políticas empresariales. El Departamento de Recursos Humanos es uno de los pirales de las organizaciones para definirse y consolidarse en el mercado; su radio de acción contempla el reclutamiento, selección, compensación, beneficios sociales, higiene y seguridad en el trabajo, desarrollo organizacional, entrenamiento y desarrollo del personal, relaciones laborales, base de datos y sistemas de información, y auditoría. La gestión del Talento Humano está estrechamente relacionada con la gestión de los recursos humanos; dado que estructura indicadores normativos que permiten fortalecer los procesos de selección, desempeño, evaluación y capacitación del personal.
Keywords: RECURSOS HUMANOS; GESTIÓN; ADMINISTRACIÓN; TALENTO HUMANO